2021
DOI: 10.3390/brainsci11111377
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Auditory Feedback Gait Training Using Smart Insole on Stroke Patients

Abstract: This study aimed to assess the effect of the auditory feedback gait training (AFGT) using smart insole on the gait variables, dynamic balance, and activities of daily living (ADL) of stroke patients. In this case, 45 chronic stroke patients who were diagnosed with a stroke before 6 months and could walk more than 10 m were included in this study. Participants were randomly allocated to the smart insole training group (n = 23), in which the AFGT system was used, or to the general gait training group (GGTG) (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Such enhancements not only reflect gains in range of motion and coordination but also signify safer ambulation capabilities among participants. These findings align with the research conducted by Junghyun Kim et al (2021), which demonstrated the positive impact of auditory feedback gait training (AFGT) with smart insoles on various gait parameters and balance in chronic stroke patients. The parallel drawn between the two studies reinforces the potential of auditory stimulation in augmenting gait rehabilitation outcomes (22).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such enhancements not only reflect gains in range of motion and coordination but also signify safer ambulation capabilities among participants. These findings align with the research conducted by Junghyun Kim et al (2021), which demonstrated the positive impact of auditory feedback gait training (AFGT) with smart insoles on various gait parameters and balance in chronic stroke patients. The parallel drawn between the two studies reinforces the potential of auditory stimulation in augmenting gait rehabilitation outcomes (22).…”
Section: Discussionsupporting
confidence: 90%
“…These findings align with the research conducted by Junghyun Kim et al (2021), which demonstrated the positive impact of auditory feedback gait training (AFGT) with smart insoles on various gait parameters and balance in chronic stroke patients. The parallel drawn between the two studies reinforces the potential of auditory stimulation in augmenting gait rehabilitation outcomes (22). Further corroborating the efficacy of sensory stimulation in stroke rehabilitation, a randomized control trial by Seung-Jun Hyun and Byoung-Hee Lee (2021) elucidated the benefits of incorporating visual feedback in sit-to-stand training.…”
Section: Discussionsupporting
confidence: 90%
“…This fact suggests that gait performance does not necessarily reflect poststroke patients' capacity to maintain proactive balance. However, the other studies reported significant improvement in the proactive balance of stroke patients after enhanced gait training (combining gait training with other task-oriented balance training) (66,97). Therefore, the question of whether or not gait training has a positive effect on proactive balance is still open.…”
Section: Discussionmentioning
confidence: 99%
“…The total score was out of 56, with 41–56 indicating “good balance”, 21–40 representing “acceptable balance impairment” and a score below 20 representing “balance impairment” (Berg et al, 1995 ). The K‐BBS has excellent intra‐rater reliability of 0.98 and inter‐rater reliability of 0.97 (Kim et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%